Persepsi Konsumen Terhadap Bauran Pemasaran Produk Se’i Babi pada Rumah Makan Baun, Kecamatan Amarasi Barat - Asri, Lidiana; Y. Luruk, Maria; S. Niron, Sirilus; R. Lole, Ulrikus (Green Publisher Indonesia, 2024)
Pork is one of the commodities that is widely consumed by people in East Nusa Tenggara Province (NTT), with se'i meat as one of its superior processed products. Se'i pork, which goes through a traditional smoking process, has a distinctive taste and aroma that makes it favored by many consumers. Based on data from the Kupang City BPS in 2021, the pig population in NTT reached 2.6 million heads, and pork production reached 26.81 million tons. This makes NTT one of the regions with the highest pork production in Indonesia. Along with the increase in the pig population, the consumption of processed pork products, especially se'i, has also increased, driving the growth of the pork se'i agroindustry in the region. The city of Kupang and its surroundings has many restaurant businesses that offer pork se'i, including Baun pork se'i restaurant, which is known for its location in the West Amarasi area. However, marketing factors such as price, location, product, and promotion in the marketing mix of pork products in Baun have not been analyzed in detail. Therefore, this study was conducted to understand consumer perception of the marketing mix of pork products in Baun and the factors that affect purchase decisions. This study aims to analyze consumer perception of the marketing mix of pork in baun, analyze factors that affect consumer decision-making. Price, location, product, and promotion are factors that affect the marketing mix of pork products in Baun. The sampling method uses an accidental sampling technique, while the data collection for primary data uses a list of questions that have been prepared and secondary data is taken from related agencies. Meanwhile, the data analysis method uses binary logistics analysis. The results of the study show that the consumer perception of pork sausage is included in the level of very fondness, and the factors that affect the marketing mix of pork sausage are price, location, and promotion while the product has no effect on the marketing mix of pork sausage in Baun.